Advanced materials and nanotechnology - Idris, Jamaliah; Hamouda, Abdel Magid Salem (Universiti Putra Malaysia Press, 2000)
In this paper a comparison of properties of the main groups of engineering materials as well as the role of materials in the development of human civilization and examples of their practical applications mare presented. Technical, economical, and ecological issues are stressed for modern materials selection for various products and their elements. The principal goal of this paper is to present "a unified view of recent progress and new directions in advanced materials". Among the specific issues identified are: (i) Areas of research and development (ii) Relationship among the various types of elements of materials research and development (iii) The role of government and private sectors (iv) The effectiveness of materials infrastructure in developing and commercialization of new materials technology (v) The effectiveness of materials research and education at universities and (vi) International cooperation.